Ранній етап формування Трипільської культури - Бурдо, Н.Б. (Археологія, 1993)
У праці розглянуто початкові етапи формування Трипільської культури на Україні (етапи А та ВІ). В работе рассматривается процесс формирования трипольско-кукутенской общности. Анализ материалов культуры Кукутени-Триполье от фазы Триполье А — Прекукутени II до этапа ВI позволяет считать, что фаза Триполье А—Прекукутени II была периодом формирования Трипольско-Кукутенской культуры, когда сложился единый культурный комплекс от бассейна Сирета до бассейна Горного Тикеча. В конце фазы Триполье А — Прекукутени III в керамическом комплексе прослежены инновации,
которые получают дальнейшее развитие уже на следующем этапе культуры Кукутени—Триполье — ВI. Этап ВI является непосредственным продолжением предыдущих фаз, на нем сохраняются основные раннетрипольские традиции. Инновации на этом этапе связаны с инокультурными импульсами, в результате которых в Кукутенско-Трипольской культуре появляется расписная керамика и посуда с примесью раковины в массе. На этапе ВI в процессе расселения трипольских племен, развития традиционных форм культуры и под влиянием трансильванских и степных племен формируются различные культурные группы, на основе которых в дальнейшем складывается несколько этнокультурных образований кукутенской и трипольской линии развития трипольско-кукутенской общности. The process of the formation of Tripoiie—Kukuteni community is studing in the paper. The analysis of the materials of Kukuteni—Tripoiie culture since the phase Tripoiie A — Prekukuteni 2 till the stage B1 permits to consider the phase Tripoiie A— Prekukuteni 2 as a period of the formation of Tripoiie—Kukuteni culture in which the common cultural complex from the basin of Siret to the basin of Gorny Tikjch was formed. At the end of the phase Tripoiie A— Prekukuteni 3 are retraced the innovations in the corpus of pottery. The were developed further at the next stage of Kukuteni—Tripoiie culture — Bl. The latter is a direct prolongation of the previous phases. The main Early—Tripolian traditions are survived during this stage. The innovations on this stage are connected with the impulses of the other cultures. As a result the painted pottery and the crockery with the admixture of shell has appeared in Kukuteni—Tripoiie culture. At the stage Bl in the process of the settling of Tripolian tribes, development of traditional forms of culture and under the influence of Transilvanian and steppe tribes the different cultural groups are formed. Subsequently on the base of them the several ethnic-cultural formations of Kukuteni and Tripoiie lines of the development of Kukuteni—Tripoiie community are created.